Growth andsurvivalrateofBaung (Hemibagrus nemurus) in PeatWaterby Giving Different Amounts ofMolasses inBioflokTechnology - Nurhasim, Nurhasim; M.Tang, Usman; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT ThisresearchwasconductedfromFebruary toApril2018attheLaboratory ofAquacultureTechnology,FacultyofFisheriesandMarine,UniversityofRiau.The purposeofthisstudy wastodeterminetheeffectofdifferentmolassesonthegrowth andsurvivalrateofbaung(Hemibagrusnemurus)onbiofloctechnology inpeat swamp water. The designused was a complete randomized design with five treatmentsandthree replications.The treatmentappliedis(1) control,(2)50ml/m3, (3) 100ml/m3,(4)150ml/m3(5)200ml/m3.Provisionofthebestmolassesis100 ml/m3,withthedoseof molassesabletoincreasethegrowthandsurvivalrateof baung(Hemibagrusnemurus),Thegrowthofanaverage weightof5.72g,growthof anaverage lengthof 9.16cm,absolute weight4,48g,absolute length4.46cm, specific growthrate3.83%,feed efficiency109.99%, survival rate90.33%, floc volume7 ml/l, and optimal waterquality. Keywords: Molasses,Biofloc, Growth, SurvivalRate, Baung.